2023
DOI: 10.1108/ilt-12-2022-0369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometrical parameters on thermohydrodynamic performance of a bearing operating with nanoparticle additive oil

Abstract: Purpose Bearing performance characteristics, such as stiffness and load capacity, are related to the viscosity of the fluid circulating through the gap. Nanoparticle additives in lubricant are one way to enhance of the viscosity. This study aims to investigate the effect of nanoparticle additives on the thermohydrodynamic performance of journal bearing with different bearing parameters. Design/methodology/approach The temperature distribution is modeled using a three-dimensional energy equation. The velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In literature, there are a lot of numerical solution methods to solve the governing equations. Although finite difference methods have generally been preferred in the studies, 1,3,22,26 finite element method, 19,21,23 and finite volume method 20 have also been used by some researchers. In the numerical solution, equations are solved with the finite difference method, and the successive over-relaxation method is also applied to achieve convergence.…”
Section: Numerical Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, there are a lot of numerical solution methods to solve the governing equations. Although finite difference methods have generally been preferred in the studies, 1,3,22,26 finite element method, 19,21,23 and finite volume method 20 have also been used by some researchers. In the numerical solution, equations are solved with the finite difference method, and the successive over-relaxation method is also applied to achieve convergence.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…In the fluid film lubricated bearings, the nanolubricants enhance the journal bearings' performance and change the bearing's thermal characteristics. [1][2][3][4] Conventional lubricants composed of hydrocarbon molecules, also known as Newtonian lubricants, have been extensively used in HJB. 5,6 On the other hand, using powder as an anti-wear and minimizing friction in the lubricant has been deployed in modern industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other related studies can be found in papers. Dal et al (2023) examined the influence of geometric parameters on the thermohydrodynamic behavior of a bearing operating with oil containing nanoparticle additives. Nanoparticles have been used as additives in lubricants to enhance viscosity.…”
Section: Introductionmentioning
confidence: 99%